Alginate-based composite aerogel for chromium (III) ion adsorption and preparation method thereof

By using alginate-based composite aerogel in chromium (III) ion adsorption materials, combined with carboxymethylation modification and hydrophobic modification, the problems of limited adsorption capacity and hydration film obstacles of existing adsorption materials are solved, and the problem of hydration film obstacles is achieved. Highly efficient and direct chromium (III) ion adsorption effect.

CN119455904AInactive Publication Date: 2025-02-18SUZHOU NINGYAN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411376410.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing chromium (III) ion adsorption materials have problems such as limited adsorption capacity, poor selectivity, difficulty in regeneration, and hydrated films hinder adsorption efficiency.

Method used

Alginate-based composite aerogel is used to optimize the pore structure and surface properties through carboxymethylation modification and hydrophobic modification, combining iron oxide and hydrophobic activated carbon, and forming an efficient chromium (III) ion adsorption material.

Benefits of technology

It significantly improves the adsorption efficiency and capacity of chromium (III) ions, breaks the limitations of the hydrated film, promotes direct contact between chromium (III) ions and the aerogel surface, and improves the adsorption rate and saturation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455904A_ABST
    Figure CN119455904A_ABST
Patent Text Reader

Abstract

The invention discloses alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method of the alginate-based composite aerogel, relates to the technical field of environment-friendly materials, and particularly discloses the alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method of the alginate-based composite aerogel. The composite aerogel is prepared by carboxymethylation modification and hydrophobic modification of alginate, and combination of waste textile converted activated carbon and an iron oxide additive through a special process. The aerogel has an excellent pore structure and surface properties, and the adsorption capacity and efficiency of the aerogel on chromium (III) ions are remarkably enhanced; compared with a traditional adsorption material, the adsorption material provided by the invention not only overcomes the obstruction of a hydration membrane to the adsorption process, but also improves the adsorption capacity and selectivity, and realizes efficient and rapid removal of chromium (III) ions in wastewater; the preparation method is simple, the cost is controllable, the application prospect is wide, and an innovative solution is provided for environmental protection and heavy metal pollution abatement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel adsorption, and in particular to an alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof. Background Art

[0002] With the rapid development of industrialization, heavy metal pollution has become one of the environmental problems that need to be solved urgently worldwide. Among them, chromium pollution is particularly prominent, because chromium is widely used in many industries such as electroplating, leather making, and chemical industry, and its wastewater discharge is large and difficult to degrade naturally. Chromium exists in the environment in various forms, including hexavalent chromium (Cr(VI)) and trivalent chromium (Cr(III)). Although trivalent chromium has relatively low toxicity, its accumulation in water bodies still poses a potential threat to aquatic organisms and human health. Therefore, the development of efficient and economical chromium (III) ion adsorption materials is of great significance for environmental protection.

[0003] Traditional chromium (III) ion adsorption materials mainly include activated carbon, resin, mineral materials, etc. These materials can adsorb chromium (III) ions to a certain extent, but there are problems such as limited adsorption capacity, poor selectivity, and difficulty in regeneration. In particular, in aqueous solution, a hydration film is easily formed on the surface of the adsorption material, which will hinder the direct contact between chromium (III) ions and the material surface, thereby reducing the adsorption efficiency. Therefore, how to overcome the influence of the hydration film and improve the adsorption efficiency and capacity of chromium (III) ions has become a hot spot and difficulty in current research.

[0004] In recent years, aerogel, as a new type of porous material, has attracted extensive attention due to its high specific surface area, low density and excellent physical and chemical properties. However, the application of aerogel in the field of chromium (III) ion adsorption still faces many challenges, such as how to optimize the pore structure, surface properties and adsorption mechanism of aerogel. In particular, traditional aerogels are often limited by the hydration membrane during the adsorption process, resulting in low adsorption efficiency.

[0005] Therefore, it is necessary to provide an alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof to solve the above technical problems. Summary of the invention

[0006] The invention overcomes the shortcomings of the prior art and provides an alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof.

[0007] 2. To achieve the above object, the technical solution adopted by the present invention is: an alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof, comprising the following steps:

[0008] S1. Extracting alginate from seaweed and treating it with sodium hydroxide solution;

[0009] S2. converting the extracted alginate into alginic acid and performing carboxymethyl modification on the alginate;

[0010] S3. introducing a hydrophobic modifier to modify the surface of alginate to increase its hydrophobicity;

[0011] S4. Converting waste textile cellulose into activated carbon and performing surface modification on it;

[0012] S5. preparing iron oxide as a metal oxide additive;

[0013] S6. mixing the modified alginate, hydrophobic activated carbon and iron oxide in a specific mass ratio and dissolving them in a mixed solvent to form a precursor solution;

[0014] S7. The precursor solution is mixed with a calcium chloride solution to form a gel, which is then freeze-dried and heat-treated, and finally subjected to additional hydrophobic treatment to obtain an alginate-based composite aerogel.

[0015] In a preferred embodiment of the present invention, in S1, the seaweed is treated with a 0.05-0.15 M sodium hydroxide solution at 50-70° C. for 1.5-2.5 h.

[0016] In a preferred embodiment of the present invention, in S2, alginate is reacted with 0.4-0.6M hydrochloric acid, the pH is adjusted to 6.8-7.2 to obtain alginate, and further carboxymethylation modification is carried out at room temperature using 0.08-0.12M chloroacetic acid and an equal concentration of sodium hydroxide for 1.5-2.5h.

[0017] In a preferred embodiment of the present invention, in said S3, the hydrophobic modifier introduced is a silane coupling agent or a long-chain fatty acid.

[0018] In a preferred embodiment of the present invention, in S4, waste textile cellulose is activated at 750-850° C. for 1.5-2.5 h to obtain activated carbon, and the surface of the activated carbon is coated with silane.

[0019] In a preferred embodiment of the present invention, in S5, iron oxide is prepared by chemical precipitation, using a 0.8-1.2M ferric chloride solution to react with an equal concentration of sodium hydroxide solution, and after precipitation, calcining at 450-550°C for 1.5-2.5h.

[0020] In a preferred embodiment of the present invention, in S6, the modified alginate, hydrophobic activated carbon and iron oxide are mixed in a mass ratio of 1:1:0.1, and ethanol or acetone is used as a mixed solvent in a ratio of 1:1-3:1, and stirred and dissolved at 55-65°C for 1.5-2.5h.

[0021] In a preferred embodiment of the present invention, in S7, the precursor solution is mixed with a 0.08-0.12M calcium chloride solution, stirred at room temperature for 25-35 minutes to form a gel, then frozen at -25--15°C for 20-28 hours, freeze-dried for 44-52 hours, and finally heat treated at 110-130°C for 1.5-2.5 hours.

[0022] In a preferred embodiment of the present invention, in said S7, the surface of the obtained aerogel is impregnated to form a thin layer of organic silicon or fluoride.

[0023] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0024] (1) The present invention provides an alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof, which significantly enhances the adsorption capacity of chromium (III) ions and effectively solves the problem that the hydration film of traditional aerogels hinders the direct contact of chromium (III) ions during the adsorption process; specifically, through specific modification technology and structural design, two core purposes are achieved: one is to enhance the adsorption efficiency and capacity of chromium (III) ions; the other is to break the limitation of the hydration film and promote the direct and efficient contact between chromium (III) ions and the aerogel surface.

[0025] (2) The alginate-based composite aerogels of the present invention adopt a dual strategy of carboxymethylation modification and hydrophobicity modification, which significantly improves their surface properties and chemical activity. Carboxymethylation increases the hydrophilicity and active sites of the aerogels and enhances the interaction with ions in water; while the hydrophobicity modification increases the affinity of the aerogels for hydrophobic pollutants, including certain forms of chromium (III) ions, by introducing non-polar groups; directly improves the adsorption efficiency and capacity of the aerogels for chromium (III) ions, enabling them to reach a higher adsorption saturation in a shorter time; compared with unmodified alginate aerogels, the composite aerogels of the present invention have significantly improved adsorption rate and adsorption amount.

[0026] (3) The present invention provides an alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof, which effectively solves the problem that the hydration film hinders the direct contact between the chromium (III) ions and the aerogel surface; the formation of the hydration film is a common phenomenon in many adsorption processes, which hinders the effective contact between the adsorbate and the adsorbent and reduces the adsorption efficiency; the present invention reduces the formation of the hydration film or accelerates its rupture by adjusting the pore structure and surface properties of the aerogel, so that the chromium (III) ions can more easily approach and adsorb on the aerogel surface; this improvement directly improves the contact efficiency between the chromium (III) ions and the aerogel surface, accelerates the adsorption process, and improves the adsorption efficiency.

[0027] (4) The present invention successfully achieves efficient adsorption of chromium (III) ions and solves the problem of hydration membrane obstruction through carboxymethylation modification and hydrophobicity modification as well as optimization of preparation process and structural design; the achievement of these two goals promotes and complements each other, and together constitutes the unique advantages and significant benefits of the present invention; overall, it not only improves the efficiency and effect of wastewater treatment, but also promotes the recycling of resources and environmental protection, providing strong support for the control and treatment of chromium pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 It is a schematic diagram of a preferred embodiment of the present invention; DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0032] like Figure 1As shown, the present invention provides an alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof, comprising the following steps:

[0033] S1. Extracting alginate from seaweed, treating the seaweed with 0.05-0.15 M sodium hydroxide solution at 50-70° C. for 1.5-2.5 h;

[0034] S2. reacting alginate with 0.4-0.6 M hydrochloric acid, adjusting the pH to 6.8-7.2 to obtain alginate, and further carboxymethylating it with 0.08-0.12 M chloroacetic acid and an equal concentration of sodium hydroxide at room temperature for 1.5-2.5 h;

[0035] S3. Introducing a hydrophobic modifier to modify the surface of alginate to increase its hydrophobicity, wherein the introduced hydrophobic modifier is a silane coupling agent or a long-chain fatty acid;

[0036] S4. Activating waste textile cellulose at 750-850° C. for 1.5-2.5 h to obtain activated carbon, and coating the surface of the activated carbon with silane;

[0037] S5. Iron oxide was prepared by chemical precipitation, using a 0.8-1.2M ferric chloride solution and an equal concentration of sodium hydroxide solution to react, and after precipitation, calcined at 450-550°C for 1.5-2.5h;

[0038] S6. The modified alginate, hydrophobic activated carbon and iron oxide are mixed, the mass ratio of alginate to hydrophobic activated carbon is in the range of 0.9:1.1-1.1:0.9, the mass of iron oxide accounts for the total mass of alginate and hydrophobic activated carbon in the range of 0.08-0.12, and ethanol or acetone is used as a mixed solvent in a ratio of 1:1-3:1, and the mixture is stirred and dissolved at 55-65°C for 1.5-2.5h to form a precursor solution;

[0039] S7. Mix the precursor solution with a 0.08-0.12M calcium chloride solution, stir at room temperature for 25-35 minutes to form a gel, then freeze at -25--15°C for 20-28 hours, freeze-dry for 44-52 hours, and finally heat-treat at 110-130°C for 1.5-2.5 hours to impregnate the surface of the obtained aerogel and form a thin layer of silicone or fluoride to obtain an alginate-based composite aerogel.

[0040] It should be noted that:

[0041] S1: By treating seaweed with 0.05-0.15M sodium hydroxide solution at a temperature of 50-70°C, alginate can be effectively and gently extracted while maintaining the integrity of its chemical structure; providing a high-quality raw material basis for subsequent modification, ensuring the high purity and stability of alginate, thereby enhancing the performance of the final product.

[0042] S2: Converting alginate into alginic acid and performing carboxymethyl modification not only improves the hydrophilicity and reactivity of alginate, but also increases the number of its surface functional groups; this enables alginate-based composite aerogels to interact more effectively with chromium (III) ions during the adsorption process, thereby improving the adsorption efficiency and capacity. Carboxymethyl modification is one of the key steps to improve the adsorption performance of aerogels.

[0043] S3: Introducing a hydrophobic modifier to modify the surface of alginate significantly enhances the hydrophobicity of the aerogel, helps reduce the formation of hydration film, and makes it easier for chromium (III) ions to access the active sites of the aerogel, thereby improving the adsorption rate and efficiency; the hydrophobic modification also increases the water resistance and stability of the aerogel, allowing it to maintain efficient adsorption performance in complex water environments.

[0044] S4: Converting waste textile cellulose into activated carbon and modifying its surface by coating it with silane can not only achieve the recycling of waste resources, but also improve the adsorption performance and stability of activated carbon. Surface coating with silane can improve the surface structure of activated carbon, increase its specific surface area and porosity, and thus improve its adsorption capacity for chromium (III) ions; in addition, the recycling of waste textiles can also help reduce environmental pollution and waste of resources.

[0045] S5: Iron oxide is prepared by chemical precipitation method, and its particle size and morphology are controlled to provide more active centers and catalytic sites for aerogel. Iron oxide acts as an auxiliary agent or catalyst in aerogel, which can accelerate the reaction rate of chromium (III) ions with the aerogel surface and further improve the adsorption efficiency. At the same time, the introduction of iron oxide also enhances the mechanical strength and stability of aerogel, making it more durable during use.

[0046] S6: The modified alginate, hydrophobic activated carbon and iron oxide are mixed in a certain proportion and dissolved by stirring at a suitable temperature using a specific mixed solvent to form a uniform precursor solution; ensuring sufficient mixing and uniform distribution of the components, thus laying a good foundation for the subsequent gelation and freeze-drying processes; at the same time, by optimizing the proportion of the mixed solvent and the stirring conditions, the pore structure and morphology of the aerogel can be further controlled, thereby improving its adsorption performance.

[0047] S7: The precursor solution is mixed with the calcium chloride solution to form a gel, and alginate-based composite aerogel is prepared through freeze-drying and heat treatment processes; the freeze-drying process can maintain the porous structure of the aerogel, while the heat treatment can further improve its stability and adsorption performance; finally, a thin layer of silicone or fluoride is impregnated on the surface of the aerogel for additional hydrophobic treatment, which can further enhance its water resistance and adsorption capacity; these steps work together to make the alginate-based composite aerogel an efficient, stable and environmentally friendly chromium (III) ion adsorption material.

[0048] Embodiment 1:

[0049] Materials preparation:

[0050] Seaweed: Use fresh kelp as the raw material, wash and chop it for later use;

[0051] Sodium hydroxide solution: accurately prepare 0.1M sodium hydroxide solution for alginate extraction;

[0052] Hydrochloric acid: Use a 0.5 M hydrochloric acid solution to adjust the pH and prepare alginic acid from alginate;

[0053] Chloroacetic acid and sodium hydroxide: Accurately weigh 0.1M chloroacetic acid and sodium hydroxide solution of equal concentration for carboxymethylation modification of alginate;

[0054] Hydrophobic modifier: Select KH-550 as the silane coupling agent and prepare it in a ratio of 1:10 to alginate;

[0055] Waste textile cellulose: Collect and process waste cotton clothing, activate the cellulose part at 800℃ for 2h to obtain activated carbon;

[0056] Silane coating agent: organic silane TEOS is selected for surface coating of activated carbon;

[0057] Ferric chloride and sodium hydroxide: Prepare 1.0 M ferric chloride solution and sodium hydroxide solution of equal concentration for preparing iron oxide by chemical precipitation method;

[0058] Ethanol and acetone: mixed in a volume ratio of 1:2 and used as a mixed solvent for the preparation of the precursor solution;

[0059] Calcium chloride solution: Prepare an accurate 0.1 M calcium chloride solution for the gelation process.

[0060] Implementation steps:

[0061] S1: Add chopped seaweed to 0.1 M sodium hydroxide solution, stir at 60 °C for 2 h, filter and collect the filtrate to obtain alginate solution;

[0062] S2: reacting the alginate solution with 0.5M hydrochloric acid, adjusting the pH to 7.0, to obtain an alginate precipitate. Redissolve the alginate precipitate in water, add 0.1M chloroacetic acid and an equal concentration of sodium hydroxide solution, and stir at room temperature for 2h for carboxymethylation modification;

[0063] S3: Mix the carboxymethylated alginate solution with the silane coupling agent KH-550 and stir at room temperature for 1 h to allow the silane coupling agent to evenly cover the alginate surface;

[0064] S4: Activating waste textile cellulose at 800°C for 2h to obtain activated carbon, and then surface coating the activated carbon with organosilane TEOS under vacuum conditions;

[0065] S5: mixing a 1.0 M ferric chloride solution with an equal concentration of a sodium hydroxide solution to generate an iron hydroxide precipitate, and calcining the precipitate at 500° C. for 2 h to obtain an iron oxide powder;

[0066] S6: The modified alginate, hydrophobic activated carbon and iron oxide were mixed in a mass ratio of 1:1:0.1, and a mixed solvent of ethanol and acetone in a volume ratio of 1:2 was added, and stirred at 60°C for 2h to form a uniform precursor solution;

[0067] S7: The precursor solution was mixed with 0.1M calcium chloride solution and stirred at room temperature for 30 min to form a gel. The gel was frozen at -20°C for 24 h and then freeze-dried for 48 h. The dried aerogel was heat-treated at 120°C for 2 h and a thin layer of silicone was impregnated on its surface to obtain the final alginate-based composite aerogel.

[0068] Embodiment 2:

[0069] This embodiment is basically the same as the first embodiment, except that: S1-S3 are removed, and in step S6, the hydrophobic activated carbon and iron oxide are mixed in a mass ratio of 1:0.1, a mixed solvent of ethanol and acetone in a volume ratio of 1:2 is added, and the mixture is stirred at 60°C for 2h to form a uniform precursor solution.

[0070] Embodiment three:

[0071] This embodiment is basically the same as the first embodiment, except that in step S6, the mass ratio is adjusted to alginate: hydrophobic activated carbon: iron oxide = 0.8:1.2:0.1, and the remaining steps are the same as S6.

[0072] Embodiment 4:

[0073] This embodiment is basically the same as the first embodiment, except that in step S6, the mass ratio is adjusted to alginate: hydrophobic activated carbon: iron oxide = 0.7:1.3:0.1, and the remaining steps are the same as S6.

[0074] Embodiment five:

[0075] This embodiment is basically the same as the first embodiment, except that in step S6, the mass ratio is adjusted to alginate: hydrophobic activated carbon: iron oxide = 0.5:1.5:0.1, and the remaining steps are the same as S6.

[0076] Experiment 1:

[0077] Adsorption performance test

[0078] The prepared aerogel was used for the adsorption experiment of chromium (III) ions using a 0.1 M chromium (III) ion solution with the pH adjusted to 5.0 and the contact time set to 2 h to evaluate its adsorption efficiency.

[0079]

[0080]

[0081] The above experiment systematically evaluated the effect of material composition on adsorption efficiency by comparing the adsorption performance of alginate-based composite aerogels composed of alginate, hydrophobic activated carbon and iron oxide in different mass ratios on chromium (III) ions. The experimental results show that Example 1 (alginate: hydrophobic activated carbon: iron oxide mass ratio of 1.0:1.0:0.1) exhibits the best adsorption efficiency among all the examples, which is summarized as follows:

[0082] Best adsorption efficiency: Example 1 has an adsorption efficiency of 90.23% which is significantly better than other examples, which is attributed to its appropriate component ratio. Alginate, as the main matrix of the composite aerogel, not only provides abundant functional groups for ion exchange and adsorption, but also the addition of hydrophobic activated carbon and iron oxide further enhances the adsorption capacity and selectivity of the material.

[0083] Adsorption capacity and residual concentration: The adsorption capacity of Example 1 reached 45.12 mg / g, which is much higher than that of other examples, indicating that it can adsorb more chromium (III) ions per unit mass. Correspondingly, the residual concentration of the solution is the lowest, only 9.78 mg / L, indicating that it has the most significant effect on the removal of pollutants.

[0084] Influence of component ratio: With the decrease of alginate ratio (Examples 2 to 5), the adsorption efficiency and adsorption capacity both showed a downward trend. This shows that alginate plays a key role in the composite aerogel, and the reduction of its content directly affects the adsorption performance of the material. Although hydrophobic activated carbon and iron oxide also have certain adsorption capacity, their effects cannot be fully exerted without sufficient alginate support.

[0085] In summary, Example 1 showed the best performance in the chromium (III) ion adsorption experiment by virtue of its optimal mass ratio of alginate, hydrophobic activated carbon and iron oxide (1.0:1.0:0.1). This discovery is of great significance for promoting the development of the field of environmental protection, especially in the treatment of water pollution.

[0086] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. An alginate-based composite aerogel for chromium (III) ion adsorption and a preparation method thereof, characterized in that: The following steps are involved: S1. Extracting alginate from seaweed and treating it with sodium hydroxide solution; S2. converting the extracted alginate into alginic acid and performing carboxymethyl modification on the alginate; S3. introducing a hydrophobic modifier to modify the surface of alginate to increase its hydrophobicity; S4. Converting waste textile cellulose into activated carbon and performing surface modification on it; S5. preparing iron oxide as a metal oxide additive; S6. mixing the modified alginate, hydrophobic activated carbon and iron oxide in a specific mass ratio and dissolving them in a mixed solvent to form a precursor solution; S7. The precursor solution is mixed with a calcium chloride solution to form a gel, which is then freeze-dried and heat-treated, and finally subjected to additional hydrophobic treatment to obtain an alginate-based composite aerogel.

2. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In the S1, the seaweed is treated with a 0.05-0.15 M sodium hydroxide solution at 50-70° C. for 1.5-2.5 hours.

3. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In the S2, alginate is reacted with 0.4-0.6M hydrochloric acid, and the pH is adjusted to 6.8-7.2 to obtain alginate, which is further carboxymethylated using 0.08-0.12M chloroacetic acid and an equal concentration of sodium hydroxide at room temperature for 1.5-2.5 hours.

4. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In S3, the introduced hydrophobic modifier is a silane coupling agent or a long-chain fatty acid.

5. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In the S4, the waste textile cellulose is activated at 750-850° C. for 1.5-2.5 h to obtain activated carbon, and the surface of the activated carbon is coated with silane.

6. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In S5, iron oxide is prepared by chemical precipitation, using a 0.8-1.2M ferric chloride solution to react with an equal concentration of sodium hydroxide solution, and after precipitation, calcining at 450-550°C for 1.5-2.5h.

7. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In the S6, the mass ratio of alginate to hydrophobic activated carbon is in the range of 0.9:1.1-1.1:0.9, the mass of iron oxide accounts for 0.08-0.12 of the total mass of alginate and hydrophobic activated carbon, and ethanol or acetone is used as a mixed solvent in a ratio of 1:1-3:1, and the mixture is stirred and dissolved at 55-65°C for 1.5-2.5h.

8. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In the S7, the precursor solution is mixed with a 0.08-0.12M calcium chloride solution, stirred at room temperature for 25-35 minutes to form a gel, then frozen at -25--15°C for 20-28 hours, freeze-dried for 44-52 hours, and finally heat treated at 110-130°C for 1.5-2.5 hours.

9. The alginate-based composite aerogel for chromium (III) ion adsorption and the preparation method thereof according to claim 1, characterized in that: In S7, a thin layer of organic silicon or fluoride is impregnated on the surface of the obtained aerogel to form a thin layer.